How Consumer Confidence, Corruption and Credit Rating Effect the Exchange Rate: Emerging Market Perspective - Ghulam Mujtaba Chaudhary; Dr. Muhammad Asif Khan; Dr. Khalid Latif (Journal of Accounting and Finance in Emerging Economies, 2020)
The paper empirically examines whether the international rating influences the rate of exchange of an economy in the long run? The paper employs Autoregressive Distributed Lag (ARDL) Bounds testing methodology on the exchange rate of China and contemporary international rating, using time series data from 1996Q1 to 2016Q4. The empirical analysis confirms the presence of a cointegration relationship between country rating and the exchange rate. To be more specific; corruption index, credit rating, and inflation are significantly and negatively cointegrated with the exchange rate of China. Conversely, consumer confidence is uncorrelated with the exchange rate over the long run. The paper focuses only on the exchange rate of CNY-USD; this may limit the generalizability of results for exchange rate with other nations. Nevertheless, the results add to the exchange rate determinants literature by including country-rating indicators in the analysis. Prior literature documents that there is some relationship between inflation and exchange rate. This research is novel in the application of robust ARDL and bounds testing to examine the long and short-run association of country rating of China with its exchange rate, after controlling for inflation.